Incorporated Companies’ Tendency to Going Public, the Problems Encountered during going Public and a review toward Resolution of these Problems: the Gaziantep Sample - Cihangir, Mehmet (Information Management and Business Review, 2014)
Public offering is a direct financing method that incorporated companies refer to in order to meet the increasing capital needs. It appears a significant event to us since such a financing method can be used for smaller companies as well as larger ones. It’s the most concrete example is the Emerging Companies Market (ECM) that sets the stage for those companies, incorporated in Istanbul Stock Exchange (ISE) and having the potential to develop and grow, to obtain fund from capital markets. The objective of this study is to investigate the tendency of incorporated companies functioning in the field of production in the province of Gaziantep, which is one of the most important industrial city in Turkey, to going public; the problems encountered by companies that want to go public and to make a general evaluation toward the resolutions of these problems. In the scope of this study, 99 incorporated companies were surveyed, the findings achieved as a result of these evaluations demonstrated that the companies within the scope of study had insufficient information about going public and consequently remained abstained concerning going public.